Pendampingan Pemberdayaan Usaha Mikro Kecil dan Menengah Berbasis Kesetaraan Gender Bagi Warga Terdampak Proyek PLN Cisokan Kabupaten Bandung Barat - Bhaskara, Ignasius Loyola Adhi; Deti, Regina; Wiharani, Annisa Paramita; Agastya, Dyah Ayunda; Maurits, Reisha Hermana (Universitas Ekuitas Indonesia, 2024)
The construction of the Cisokan Hydroelectric Power Plant (PLTA) in West Bandung Regency has significantly impacted the surrounding community. Even though it increases electricity availability and provides economic benefits, this project also raises problems, especially for women's communities, including issues of violence, sexual harassment, and gender inequality, by referring to the values of Sustainable Development Goals (SDGs) #1 (Eradicating Poverty) and #5 (Gender Equality). This service aimed to empower women through increasing knowledge and skills in the community, especially vulnerable groups such as women, to strengthen their social resilience against the negative impacts of social issues and gender inequality in hydropower development. Activities involved training, mentoring, and Focus Group Discussions (FGD) with the participation of 54 Fatayat NU cadres in Rongga Village and Cipongkor Village. The results included increased women's organizing, increased financial management and digital marketing skills of local MSMEs, and confirmation of residents' situation through FGDs. The potential for sustainability of this program was immense through the involvement of Fatayat NU and PLN in continuing existing activities and organizing. Keyword: Inequality, Gender, SDGs, MSMEs, empowerment Abstrak Pembangunan Pembangkit Listrik Tenaga Air (PLTA) Cisokan di Kabupaten Bandung Barat memberikan dampak signifikan terhadap masyarakat sekitar. Meskipun meningkatkan ketersediaan listrik dan memberikan manfaat ekonomi, proyek ini juga menyulut permasalahan, terutama terhadap komunitas perempuan, termasuk isu kekerasan, pelecehan seksual, dan ketidaksetaraan gender dengan merujuk pada nilai-nilai Sustainable Development Goals (SDGs) #1 (Menghapus Kemiskinan) dan #5 (Kesetaraan Gender). Pengabdian ini bertujuan untuk pemberdayaan perempuan melalui penambahan pengetahuan dan keterampilan kepada masyarakat, terutama kaum rentan seperti perempuan, guna memperkuat ketahanan sosial mereka terhadap dampak negatif isu sosial dan ketidaksetaraan gender dalam pembangunan PLTA. Metode pengabdian meliputi observasi, pelatihan, pendampingan, dan Focus Group Discussion (FGD) dengan partisipasi 54 kader Fatayat NU di Desa Rongga dan Desa Cipongkor. Hasil pengabdian mencakup pengorganisasian perempuan yang lebih terstruktur, peningkatan keterampilan dalam pengelolaan finansial dan pemasaran digital UMKM masyarakat sekitar, serta konfirmasi situasi yang dihadapi oleh warga melalui FGD. Potensi keberlanjutan program ini sangat besar melalui keterlibatan Fatayat NU dan PLN dalam melanjutkan kegiatan serta pengorganisasian yang sudah terjalin. Kata kunci: Ketidaksetaraan, Gender, SDGS, UMKM, pemberdayaan